Age‐dependent compressive strength and elastic modulus of fly ash‐based geopolymer concrete. (23rd November 2020) - Hassan, Amer; Arif, Mohammed; Shariq, M.
Abstract: This paper presents an experimental and analytical study on the age‐dependent mechanical properties of geopolymer concrete. The effect of total aggregate content and the ratio of sand‐to‐total aggregate content on the engineering properties of geopolymer concrete has been investigated. Geopolymer concrete cubes, prisms, and cylinders were prepared and tested for evaluation of the engineering properties of geopolymer concrete at the times of 3, 7, 28, 56, 90, and 180 days. The experimentally obtained results showed that the combination of 70% of the total aggregate by volume and 0.35 by weight the ratio of sand‐to‐total aggregate had been given the maximum strength of fly ash‐based geopolymer concrete. The assessment of available models for the calculation of age‐dependent modulus of elasticity and compressive strength with experimental results has been studied as well. An analytical model has been suggested for predicting the modulus of elasticity and compressive strength of geopolymer concrete at any age. The proposed models showed a good match with the experimental results. The present experimental and analytical study will be helpful in the production and design of geopolymer concrete structures.